Discussion on the Mechanism of Gandoufumu Decoction Attenuates Liver Damage of Wilson's Disease by Inhibiting Autophagy through the PI3K/Akt/mTOR Pathway Based on Network Pharmacology and Experimental Verification - Lulu Tang; Chenling Zhao; Jing Zhang; Ting Dong; Huaizhen Chen; Taohua Wei; Jiuxiang Wang; Wenming Yang (Hindawi Limited, 2023)
Background. Gandoufumu decoction (GDFMD) is a traditional Chinese medicine that has been widely used to treat Wilson's disease (WD) liver damage patients. However, its specific molecular mechanism currently remains unclear. Autophagy as a key contributor to WD liver damage has been intensely researched in the recent years. Therefore, the aim of this present study is to explore the effect of GDFMD on autophagy in WD liver damage, and the final purpose is to provide scientific evidence for GDFMD treatment in WD liver damage. Methods. The molecular mechanisms and autophagy-related pathways of GDFMD in the treatment of WD liver damage were predicted using network pharmacology. Copper assay kit was used to determine copper content in serum. Enzyme-linked immunosorbent assay (ELISA) was utilized to quantify serum levels of liver enzymes and oxidative stress-related indicators. Hematoxylin-eosin (HE), Masson, and Sirius red staining were used for the characterization of liver pathological changes. Transmission electron microscopy, immunofluorescence, and Western blot analyses were used to evaluate autophagy activity. The impact of the GDFMD on typical autophagy-related pathway (PI3K/Akt/mTOR pathway) molecules was also assessed via Western blot analysis. Results. GDFMD effectively attenuated serum liver enzymes, oxidative stress, autophagy, and degree of hepatic histopathological impairment and reduced serum copper content. Through network pharmacological approaches, PI3K/Akt/mTOR pathway was identified as the typical autophagy-related pathway of GDFMD in the treatment of WD liver damage. Treatment with GDFMD activated the PI3K/Akt/mTOR pathway, an effect that was able to be counteracted by LY294002, a PI3K antagonist or Rapa (rapamycin), an autophagy inducer. Conclusions. GDFMD imparted therapeutic effects on WD through autophagy suppression by acting through the PI3K/Akt/mTOR pathway.